Immunomodulatory Activity In Vitro and In Vivo of a Sulfated Polysaccharide with Novel Structure from the Green Alga Ulvaconglobata Kjellman - Sujian Cao; Yajing Yang; Shan Liu; Zhuling Shao; Xiao Chu; Wenjun Mao (Marine Drugs, 2022)
Algae accumulate large amounts of polysaccharides in their cell walls or intercellular regions. Polysaccharides from algae possess high potential as promising candidates for marine drug development. In this study, a sulfated polysaccharide, UCP, from the green alga Ulva conglobata Kjellman was obtained by water extraction, anion-exchange, and size-exclusion chromatography purification, and its structure was characterized by a combination of chemical and spectroscopic methods. UCP mainly consisted of →4)-α/β-l-Rhap-(1→, →4)-β-d-Xylp-(1→ and →4)-β-d-GlcAp-(1→ residues. Sulfate ester groups were substituted mainly at C-3 of →4)-l-Rhap-(1→ and C-2 of →4)-β-d-Xylp-(1→. Partial glycosylation was at C-2 of →4)-α-l-Rhap-(1→ residues. UCP possessed a potent immunomodulatory effect in vitro, evaluated by the assays of lymphocyte proliferation and macrophage phagocytosis. The immunomodulatory activity of UCP in vivo was further investigated using immunosuppressive mice induced by cyclophosphamide. The results showed that UCP markedly increased the spleen and thymus indexes and ameliorated the cyclophosphamide-induced damage to the spleen and thymus. UCP could increase the levels of white blood cells, lymphocytes, and platelets, and improve the hematopoietic inhibition caused by cyclophosphamide. Moreover, UCP significantly promoted the secretions of the immunoglobulin (Ig)G, IgE, and IgM. The data demonstrated that UCP is a novel sulfated polysaccharide and may be a promising immunomodulatory agent.